Застосування пероксидованих полісахаридів для одержання гідрогелевих композитів - Чобіт, М. Р.; Chobit, M. R. (Lviv Politechnic Publishing House, 2018)
Одержано гідрогелеві композитні матеріали, які можна застосувати для вироб- ництва косметичних виробів та матеріалів медичного призначення. Композити одержано на основі пероксидованих полісахаридів та поліакриламіду, які, як відомо, є біосумісними та нетоксичними. Було досліджено кінетику набрякання одержаних гідрогелевих композитів. Одержані гідрогелі демонструють міцну тривимірну структуру, яка володіє значними показниками сорбуючої здатності у водному середо- вищі. За тривалого зберігання у воді ці гідрогелеві композитні матерали зберігають свою форму.

In carrying out this work, hydrogel composite materials were obtained which can be used in the manufacture of cosmetic products and medical supplies. The presented composites were obtained on the basis of peroxidated polysaccharides (starch, cellulose) and polyacrylamide, which as is generally known are biocompatible and non-toxic. The kinetics of swelling of the obtained hydrogel composites was researched. The obtained hydrogels demonstrate a strong, sewn, three-dimensional structure that possess significant indexes of sorption ability in an aqueous medium. In the prolonged storage in water, these hydrogel composite materials save their form.
Application of peroxidated polyescarides for the obtain of hydrogel composites
Keywords: гідрогелі; поліакриламід; полісахариди; пероксидна модифікація; hydrogel; polyacrylamide; polysaccharides; peroxide modification